THE USE OF BOARD RACE GAMES TOWARD THE IMPROVEMENT OF STUDENTS VOCABULARY’S MEMORIZATION AT THE FIRST YEAR STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR - Rahmadani, Femy; Pammu, Abidin; Nasmilah, Nasmilah (JURNAL ILMU BUDAYA, 2021)
This study focuses on board race games in which students of the English Education Department in the first years at UIN Alauddin Makassar can improve vocabulary memories. This study is planned in the first year of students from the UIN Department of English Education to discover the efficiency of the use of Board Race Games to develop their vocabulary. The study used a quasi-experimental method of two before and after the test classes. In this analysis there were 2 variables; they are independent (Using Board Race Games) and contingent (Memorization of Vocabulary). This research instrument is a test aimed at evaluating the students' success in vocabulary memory. The research is performed both before and after testing. In the post-test, the analysis of the mean score between the test class and the control class has ensured whether the technique is successful.